A Systematic Review of Bioactive Metabolites and Antioxidant Potential of Sawo Duren (Chrysophyllum spp.): Integrating Evidence from Metabolomic and Chemometric Studies - Fadillah Maryam Bau Agiel; Any Guntarti; Warsi Warsi; Abdul Halim Umar (Postgraduate, University of Mataram, 2026)
Chrysophyllum spp. contains diverse bioactive metabolites, including polyphenols, flavonoids, and triterpenes such as lupeol, which contribute to their antioxidant, antiparasitic, and cytotoxic activities. However, most existing studies rely on basic phytochemical analyses and have not incorporated metabolomic or chemometric approaches capable of providing comprehensive metabolite profiling. This systematic review synthesizes current evidence on the bioactive metabolites and antioxidant potential of Chrysophyllum spp. and evaluates the extent to which advanced analytical techniques have been applied. The included studies report high levels of polyphenols and triterpenes, with notable antioxidant effects mediated through enhanced SOD, CAT, and GPx activities and reduced oxidative stress. Polyphenolic compounds also exhibit cytotoxicity via ROS induction in cancer cells, while lupeol and its derivatives demonstrate promising antiparasitic activity. Despite these findings, the lack of high-resolution metabolomics and chemometric integration limits the identification of key metabolites and mechanistic understanding. Overall, Chrysophyllum spp. represent a potential natural source of biologically active metabolites, particularly antioxidants. Future research using advanced metabolomic and the chemometric methodologies is essential to achieve comprehensive metabolite mapping and clarify the mechanisms underlying their bioactivities.